2015
DOI: 10.1016/j.molcel.2015.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Top3-Rmi1 DNA Single-Strand Decatenase Is Integral to the Formation and Resolution of Meiotic Recombination Intermediates

Abstract: Summary The topoisomerase III (Top3)-Rmi1 heterodimer, which catalyzes DNA single strand passage, forms a conserved complex with the Bloom's helicase (BLM, Sgs1 in budding yeast). This complex has been proposed to regulate recombination by disassembling double-Holliday junctions in a process called dissolution. Top3-Rmi1 has been suggested to act at the end of this process, resolving hemicatenanes produced by earlier BLM/Sgs1 activity. We here show that, to the contrary, Top3-Rmi1 acts in all meiotic recombina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
167
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(179 citation statements)
references
References 70 publications
12
167
0
Order By: Relevance
“…Disruption of the recombination program can also result in more complex forms of JMs (Oh et al 2007;Kaur et al 2015;Tang et al 2015). We found that the JM lifespan in nup2D (0.6 hr) was longer than that in WT (0.3 hr), but not to the extent of ndj1D (1.6 hr; Figure 6C).…”
Section: Deleting Spo11 Bypasses the Block To Forming Nuclear Divisionsmentioning
confidence: 84%
See 3 more Smart Citations
“…Disruption of the recombination program can also result in more complex forms of JMs (Oh et al 2007;Kaur et al 2015;Tang et al 2015). We found that the JM lifespan in nup2D (0.6 hr) was longer than that in WT (0.3 hr), but not to the extent of ndj1D (1.6 hr; Figure 6C).…”
Section: Deleting Spo11 Bypasses the Block To Forming Nuclear Divisionsmentioning
confidence: 84%
“…These two phenotypes are similar to the meiotic depletion alleles of top3/rmi1 that disrupt decatenase activity and lead to the accumulation of unresolved JMs. These mutations block nuclear divisions without disrupting the meiotic program, also known as "meiotic catastrophe" (Gangloff et al 1999;Jessop and Lichten 2008;Oh et al 2008;Kaur et al 2015;Tang et al 2015). Similar to the top3/rmi1 mutants, deletion of SPO11 or mutating the catalytic residue of SPO11 (SPO11-Y135F) suppressed the nup2D ndj1D block to nuclear divisions, presumably by eliminating a physical constraint caused by intermediates, or aberrant structures, associated with meiotic recombination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sgs1 is known to interact with the topoisomerase complex Top3-Rmi1 in a variety of processes including 59 to 39 strand resection during homologous recombination and dissolution of double Holliday junctions (Bennett et al 2000;Fricke et al 2001;Chang et al 2005;Mullen et al 2005;Ui et al 2005;Chen and Brill 2007;Cejka and Kowalczykowski 2010;Niu et al 2010). Recently Sgs1 and Top3-Rmi1 were shown to have interdependent and independent functions in meiosis (Kaur et al 2015;Tang et al 2015). However an antirecombination role for the Top3-Rmi1 complex has not been clearly established, though previous studies showed that top3D mutants increased recombination between divergent DNA sequences (Wallis et al 1989;Bailis et al 1992).…”
mentioning
confidence: 99%